Space Tourism Challenges - Polkowska, Małgorzata (Review of European and Comparative Law, 2021)
Space is a new destination for tourism. Today tourists can travel the world using many different modes of transportation, including road, maritime, and air. People always want to discover new destinations. Human beings strive to break borders and go beyond - even to the stars. There are new technical and commercial challenges and innovations in reaching outer space. The new transportation business of today has already experienced many ups and downs, but definitely big projects, such as traveling to the Moon or Mars remain the purview of the perennial space powers. The Author considers what kind of challenges space tourism brings (in the commercialization era) and what kind of space governance and policy is needed to make this tourism efficient. Some comparisons referring to airspace and outer space aspects, such as managerial, organizational, and legal have been made. The basic analysis made in this article indicates that the commercial space industry seeks to be new space operators, provided that they operate in a safe and secure manner according to international rules and policies. Good strategic planning and management of space is the key.